Near miss - Woods, Stuart; Battles, Brett (Woods, Stuart. Stone Barrington novel, 2023)
"Following a string of adventures, Stone Barrington is enjoying some downtime in New York City when a chance encounter introduces him to a charming new companion. Too bad she also comes with the baggage of a persistent ex-boyfriend intent on retribution. As Stone skillfully dodges each disturbance, it soon becomes clear that there is potentially an even more treacherous game being played behind the scenes. And when long-standing grudges resurface, Stone is brought back into the orbit of some familiar enemies. He must use all of his tricks--as well as those of a few old friends--to evade trouble before it's too late. But this time, danger just might catch him"--